2018
DOI: 10.1159/000490111
|View full text |Cite
|
Sign up to set email alerts
|

Liver Resection for Colorectal Hepatic Metastases after Systemic Chemotherapy and Selective Internal Radiation Therapy with Yttrium-90 Microspheres: A Systematic Review

Abstract: Background: Selective internal radiation therapy (SIRT) using yttrium-90 resin microspheres has been used together with systemic chemotherapy to treat patients with unresectable liver metastases. This study undertook the first systematic pooled assessment of the case profile, treatment and outcome in patients with initially inoperable colorectal hepatic metastases undergoing resection after systemic chemotherapy and SIRT. Methods: A systematic review of the literature was performed using Medline and Embase for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…It concluded that the mortality, complication and liver failure rates were similar in these patients to rates expected in patients who had not received SIRT prior to resection or transplantation. Similarly, a systematic review of the published literature found a conversion rate to hepatectomy of 13.6% in 120 patients and low surgical mortality [15]. Collectively, these studies are very relevant to multi-disciplinary teams considering SIRT to downstage tumours to subsequent resection.…”
Section: Discussionmentioning
confidence: 96%
“…It concluded that the mortality, complication and liver failure rates were similar in these patients to rates expected in patients who had not received SIRT prior to resection or transplantation. Similarly, a systematic review of the published literature found a conversion rate to hepatectomy of 13.6% in 120 patients and low surgical mortality [15]. Collectively, these studies are very relevant to multi-disciplinary teams considering SIRT to downstage tumours to subsequent resection.…”
Section: Discussionmentioning
confidence: 96%
“…There is a substantial heterogeneity of treatments, with some reports using a combination of IRE with RFA and SIRT despite the published limited efficacy of the latter intervention for the treatment of colorectal hepatic metastases [25]. In keeping with a treatment used in the metastatic setting, systemic chemotherapy is the most frequently used pre-IRE treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Selective internal radiation therapy (SIRT) with beta-particle emitting yttrium-90 bound to microspheres is another technique enabling therapy directly to the liver and thereby limiting the toxic effect of systemic treatments [33,34]. SIRT in combination with systemic therapy has been shown to enable resectability in a selected group of patients with initially unresectable CRLM [35,36]. The techniques HAIC and SIRT are not used routinely in patients with CRLM at the study centre and consequently their potential role in conversion therapy could not be evaluated in this study.…”
Section: Discussionmentioning
confidence: 99%